Thymosin α1 modifies podosome architecture and promptly stimulates the expression of podosomal markers in mature macrophages. (July 2015) - Serafino, Annalucia; Andreola, Federica; Pittaluga, Eugenia; Krasnowska, Ewa K; Nicotera, Giuseppe; Sferrazza, Gianluca; Sinibaldi Vallebona, Paola; Pierimarchi, Pasquale; Garaci, Enrico
<x xml:space="preserve">Abstract</x> Background and aims: The immunomodulatory activity of thymosin α1 (Tα1) on innate immunity has been extensively described, but its mechanism of action is not completely understood. We explored the possibility that Tα1-stimulation could affect the formation of podosomes, the highly dynamic, actin-rich, adhesion structures involved in macrophage adhesion/chemotaxis. Methods: The following methods were used: optical and scanning electron microscopy for analyzing morphology of human monocyte-derived macrophages (MDMs); time-lapse imaging for visualizing the time-dependent modifications induced at early times by Tα1 treatment; confocal microscopy and Western blot for analyzing localization and expression of podosome components; and Matrigel Migration Assay and zymography for testing MDM invasive ability and metalloproteinase secretion. Results: We obtained data to support that Tα1 could affect MDM motility, invasion and chemotaxis by promptly stimulating assembly and disassembly of podosomal structures. At very early times after its addition to cell culture medium and within 1 h of treatment, Tα1 induces modifications in MDM morphology and in podosomal components that are suggestive of increased podosome turnover. Conclusions: Since impairment of podosome formation leads to reduced innate immunity and is associated with several immunodeficiency disorders, we confirm the validity of Tα1 as a potent activator of innate immunity and suggest possible new clinical application of this thymic peptide.